The Influence of Tilawati Method Satisfaction Branch of JABODETABEK and Banten on Service Quality of Central Tilawati Method (The Analysis of Tilawati Method Training Studies) - Indah Wahyu Ningsih (At-Ta'dib, 2021)
The tilawati method is one of the fastest developing al quran methods in indonesia, by expanding its branch office in 59 cities and districts over indonesia. This thesis discusses the satisfaction felt by branch office towards central tilawati office service quality. This analysis studies was focused to tilawati training method using servQual method based on tangible, rliability, responsiveness, assurance and emphaty dimmensions .This research is intended to answer the problems  "How the quality of the central Tilawati service has been provided to the branches office on Jabodetabek and Banten". The study measures  the service gap received with the expectation of the customers whom are branch heads,trainers,teachers and representatives intitute of tilawati method users in Jabodetabek and Banten . From this result of research data gap are obtained of -0,064, its means the rating of service quality of central Tilawati is good enough. There are many things that have been felt by branches office (jabodetabek n banten) . And there are also some things that are categorized as sufficient. There are omethings that must to be fixed quickly are (1) Social media as  a learning tool, (2) Immediatly for responing branch office, (3) Simple to having Tilawati learning tool according to S.O.P, and (4) Building the innovation contemporary  in learning al quran for now and the future